Kemampuan Berpikir Kritis Dalam Pendekatan Matematika Realitik di Sekolah Dasar - Ika Sartika (Institut Agama Islam Negeri (IAIN) Curup, 2019)
Realistic mathematics learning is basically the use of reality and the environment understood by students to facilitate mathematics learning. In realistic mathematics learning things that are tangible or concrete that can be observed or understood by students imagine, while what is meant by the environment is an environment where students are located in the school, family and community environment that can be understood by students. In PMR students are invited to be active, free to express ideas and they are also expected to share their ideas meaning they are free to communicate their ideas with each other. In PMR the learning process takes place interactively, and students become the focus and all activities in the class. Whereas the teacher acts as a facilitator, helping them compare ideas and guide them to make decisions about which ideas are better for them. This learning can be used as an alternative to make learning mathematics more fun that can affect students' critical thinking. A good student's critical thinking process can be a means to form effective and communicative learning, especially for elementary students who are still thinking at a concrete level.